"It should be a constant reminder": Space, meaning and power in post-liberation Africa. (November 2022) - Cawood, Stephanie; Fisher, Jonathan
Abstract: Much of contemporary Eastern and Southern Africa is governed by former national liberation movements, each having won power after lengthy and punishing insurgencies. To varying degrees, these post-liberation governments have since commemorated their respective struggles through inscribing the landscape with a range of spatial projects – from museums and statues to vast memorial complexes. This study explores the provenance, significance, and meaning of this spatial work, and its relationship to the broader politics of post-liberation Africa. Drawing on 3.5 years of fieldwork undertaken across five countries and numerous memorialization sites, we argue that, with some exceptions, these spatial acts have been undertaken with limited consultation or debate outside of ruling elites, who approach struggle memorialization as a normative and political imperative. For these actors, these spaces are not necessarily intended to persuade domestic audiences of the "rightness" of the struggle or of the party's legitimacy to govern per se . Instead, they offer an assertion of authority, not a dialogue. This, we suggest, aligns with these governing movements' general – totalising – political mindset, whereby ensuring the continued centrality and commemoration of the struggle, and of key figures and leaders within it, is a self-evident obligation rather than a matter for wider reflection and debate.